Literature Review of Performance Management Systems and Their Impact on Employee Performance - Tulus Harefa; Rizki Agung Santoso; Luk Luk Fuadah (PT. INOVASI TEKNOLOGI KOMPUTER, 2024)
This journal presents a comprehensive literature review on Performance Management Systems (PMS) and their influence on employee performance, focusing on studies published from 2020 onwards. PMS is a crucial organizational tool designed to align individual goals with broader organizational objectives, promoting employee engagement, productivity, and overall success. Through analyzing ten scholarly articles, the review highlights several key themes: the role of PMS in enhancing employee engagement, the adaptability of PMS across various industries, and the impact of PMS on productivity. Studies suggest that well-designed PMS can lead to higher employee engagement and job satisfaction by providing clear goals and regular feedback. However, the review also discusses challenges related to PMS implementation, particularly in industries with high uncertainty, where a one-size-fits-all approach may not be effective. Additionally, the literature emphasizes the importance of flexibility within PMS, as it allows organizations to adapt to changing market conditions and employee needs. Despite its benefits, PMS can face resistance during implementation, which requires careful management of change processes. The review concludes that a successful PMS is one that is adaptable, inclusive, and integrated with organizational culture, offering valuable insights for organizations seeking to improve employee performance. Future research could explore the long-term impact of PMS on employee behavior and organizational sustainability